Implementasi Nilai-Nilai Hukum Pidana Islam dalam Konteks Ke-Indonesia-an (Kajian tentang Pembaharuan KUHP Nasional) - M. Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2001)
Basedon historical source and constitutional juridical guarantee are surely implementation the values at law of cn'minai procedure in the context of Indonesia, (c. q compiiing of Nationa Criminal Code Procedure) are quite prospective. The vaiues of prospective ana implementative Islamic criminal procedure in compung National Criminal Code Procedure for the future embrace both value deal with the concept of criminal act, criminal responsibility and criminal sanction. The values of Islamic criminal procedure which is going to be implemented should be discussed and transformed first till as national values which are accept able by the whole elements of nation.